Improvement in Productivity by Application of a Slat Conveyor Design in a Steel Rolling Mill - Khajuria, Akhil; Singh, Mayur Pratap; Raina, Ankush; Akhtar, Modassir (International Journal For Research In Mechanical & Civil Engineering, 2018)
This work introduces a novel approach to handle heated ingots without lowering down their temperature and productivity of the finished billets. The design and development of slat conveyor for angular trajectory improved the handling of heated ingots in a lot and subsequently improved mechanical properties of finished billet. Hereafter; a detailed cost and replacement analysis was performed to replace the idle or non-functioning assets by working or new resources. The critical analysis of cost includes various items such as plant running cost, replacement cost, increased output cost and total cost. A significant improvement was noticed in the plant efficiency and balance sheet after implementing the proposed slat conveyor model. Design software Pro-E was used to design the slat conveyor before implementation and subsequent cost analysis.